PWE-046 Early Clinical Experience of Endoclot™ in the Treatment of Acute Gastro-Intestinal Bleeding. (4th June 2013) - Halkerston, K; Evans, J; Ismail, D; Catnach, S; Chaudhary, R; Fullard, M; King, A; Leahy, A
Abstract : Introduction: EndoClot™ is a new novel haemostatic powder for the treatment of gastrointestinal bleeding. We report our initial experiences of EndoClot™ as an adjunct haemostatic therapy. This is the first UK report of its endoscopic use in gastrointestinal bleeding. Methods: EndoClot™ was used as an adjunct therapy in the treatment of continued bleeding following a therapeutic intervention, either for acute upper gastrointestinal bleeds, or after elective endoscopic mucosal resections. Up to 1g of AMP® (absorbable modified polymers) was applied in each patient using the EndoClot™ air compressor and applicator. Results: EndoClot™ was used in a total of 6 patients, (5 men, 1 woman; aged between 49 and 83 years, mean age 68 years). In 2 patients, EndoClot™ was applied following endoscopic mucosal resection of a rectal polyp after bleeding was not resolved with cautery. In a further 2 patients, EndoClot™ was applied over a duodenal ulcer with endoscopic stigmata of recent haemorrhage when there was residual bleeding despite adrenaline injection and gold probe cautery. In another patient, EndoClot™ was applied following clipping of a spurting vessel at the gastro-oesophageal junction (likely Mallory-Weiss tear). In these 5 patients, application of EndoClot™ resolved any continued bleeding. There was also no rebleeding within 14 days of the procedure, no mortality or major adverse events. A sixth patient had EndoClot™ applied to what was first thought to be a duodenal ulcer with a probable vessel, when there was residual bleeding despite adrenaline injection and gold probe cautery. This patient was re-scoped the following day after further bleeding and subsequent investigations confirmed a carcinoma of the pancreatic head with duodenal infiltration. Conclusion: EndoClot™ appears to be a safe and effective adjunct to existing therapies in the treatment of gastrointestinal bleeding. Large prospective studies are required to establish its exact role alongside established methods of haemostasis. Disclosure of Interest: None Declared.